Cílená mutageneze endogenního genu v genomu D. melanogaster programovatelnými nukleázami - Renner, Marek (Jihočeská univerzita, 2015)
Several techniques have recently been described for precise mutagenesis of selected target sites in the genome. This thesis establishes the method of gene targeting by CRISPR/Cas system in D. melanogaster and compares it with gene targeting using TALENs. To test the mutagenesis systems, we choose an endogenous gene encoding concentrative nucleoside transporter gene (CNT1). We have received two mutants containing large deletions affecting the N-terminal part of the CNT1 gene. We show that CRISPR/Cas is useful tool for targeted gene disruption in D. melanogaster.
Targeted mutagenesis of the endogenous gene in D. melanogaster genome by engineered nucleases
Keywords: Cílená mutageneze; programované nukleázy; TALEN; CRISPR; CNT1